(untitled) (Altre Modernità, 2024)
This analysis delves into the potential healing effect of storytelling within collective and communal contexts, drawing particularly from Affect Theory (Massumi, Sedgwick). Even familiar narratives take on different connotations when woven into the fabric of storytelling: emotional responses to narrative foster empathy and ethical engagement (Nussbaum), while the diverse ways in which stories are articulated evoke varied emotional responses (Hogan). By exploring the role played by two contemporary Australian novels, both released in 2017, by Kim Scott and Peter Carey, the following discussion underscores the physicality and centrality of space/place, as well as of certain material objects, in how these stories articulate the dynamics of emotional responses to grieving and healing.